Isolated Aspergillosis Myocardial Abscesses in a Liver-Transplant Patient. (22nd February 2014) - Dang-Tran, Kim-Diêp; Chabbert, Valérie; Esposito, Laure; Guilbeau-Frugier, Céline; Dédouit, Fabrice; Rostaing, Lionel; Rousseau, Hervé; Otal, Phillippe; Kamar, Nassim
Abstract : Cardiac abscess is an uncommon and fatal complication after transplantation. We report a case of an initially isolated aspergillosis myocardial abscess diagnosed by cardiac magnetic resonance imaging (CMRI). At that time, there was no other biological evidence or other extracardiac manifestations. A three-month course of dual antifungal therapy followed by a single antifungal therapy was empirically given. Six month after admission, Aspergillus fumigatus was isolated for the first time and the patient deceased from a disseminated aspergillosis.